2015
DOI: 10.1038/ncomms9550
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of 1,3-butadiene on platinum–copper alloys at the single-atom limit

Abstract: Platinum is ubiquitous in the production sectors of chemicals and fuels; however, its scarcity in nature and high price will limit future proliferation of platinum-catalysed reactions. One promising approach to conserve platinum involves understanding the smallest number of platinum atoms needed to catalyse a reaction, then designing catalysts with the minimal platinum ensembles. Here we design and test a new generation of platinum–copper nanoparticle catalysts for the selective hydrogenation of 1,3-butadiene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
578
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 526 publications
(598 citation statements)
references
References 56 publications
18
578
1
1
Order By: Relevance
“…In several cases it has been shown that by doping the coinage metals with PGMs at very low molar fractions, such that these more reactive metals disperse as isolated single atoms in the surface layer of the host material, the activity of the coinage metal surface can be dramatically enhanced whilst retaining excellent reaction selectivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several cases it has been shown that by doping the coinage metals with PGMs at very low molar fractions, such that these more reactive metals disperse as isolated single atoms in the surface layer of the host material, the activity of the coinage metal surface can be dramatically enhanced whilst retaining excellent reaction selectivity [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These single atom alloys (SAAs) of Sykes and co-workers exhibit tolerance to CO [18] and have been employed to catalyse hydrogenation [16][17][18][19][20], dehydrogenation [22,23], C-H activation and hydrosilylation [25] reactions with high activity and selectivity, as extended model surfaces and/or as real catalyst nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…28 A recent study revealed a direct link between single crystal and nanoparticle catalysts of Pt−Cu SAAs which show high activity and selectivity for butadiene hydrogenation to butenes, demonstrating transferability from the model study to the catalytic reaction under practical conditions. 29 Using the opposite approach, Besenbacher et al found that adding small amounts of Au to Ni(111) tempered surface reactivity and reduced catalyst coking and transferred this result to a real catalyst. 30,31 In the current work, we have alloyed small amounts of Ni into Au(111) to produce SAAs and demonstrated their potential for increasing the binding strength of adsorbates using CO as a probe molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies [27][28][29][30][31][32][33][34][35][36][37] have provided incontrovertible proof that individual atoms are indeed capable of effecting a number of catalytic reactions, especially selective hydrogenations, as well as the water-gas shift reaction:…”
Section: Single-atom Heterogeneous Catalystsmentioning
confidence: 99%